Drain's perianesthesia nursing a critical care approach - Odom-Forren, Jan; Drain, Cecil B (Elsevier/Saunders, 2013)
Drain's Perianesthesia Nursing: A Critical Care Approach, 6th Edition is the most comprehensive book on the market specifically tailored to perianesthesia nurses. The book features five distinct sections - the PACU, anatomy and physiology, pharmacology, nursing care, and special considerations. Nursing and pharmacologic interventions are integrated with in-depth coverage of pathophysiology. This edition expands coverage of evidence based research and adds a new chapter on care of the obese patient undergoing bariatric surgery. Written by Jan Odom-Forren, an expert in the anesthesia and post-operative fields, Drain's Perianesthesia Nursing is also an excellent study tool for ASPAN certification.